Regulating Financial Digital Innovation: A Study Data Sharing on Bank and Fintech Collaboration - Patria, Valentino Gola (Global Legal Review, 2025)
Banks are challenged to innovate in developing their products and services to retain their customers. One way for banks to improve their ability to develop digital financial products and services is by collaborating with fintech companies. The use of data is one of the important aspects in bank and fintech collaboration to improve digital products and services. Data sharing through Application Programming Interface (API) or known as Open Banking has been widely utilised by financial industry players, both banks and fintechs. This research aims to explore how data sharing arrangements between banks and fintechs in collaboration to develop their digital products and services. From the results of the research, currently the regulation of data sharing in the financial industry is carried out by Bank Indonesia in the payment system. In the regulation, Bank Indonesia involves SROs to create a standard known as Standard National Open API (SNAP), based on the research study, it is necessary to strengthen the regulation of several aspects including standard governing body, data governance aspects and IT risk management so that consumer protection and personal data protection can be further improved.